Protein profiling as a tool for identifying environmental aerobic endospore-forming bacteria - Paulo Henrique R Martins; Luciano Paulino da Silva; Juliana Capella de Orem; Maria Inês A de Magalhães; Danilo de Andrade Cavalcante; Marlene Teixeira De-Souza (Open Journal of Bacteriology - Peertechz Publications, 2020)
Aerobic Endospore-Forming Bacteria (AEFB) are taxonomically and physiologically diverse, comprising species of genus Bacillus and related genera of industrial and medical importance. For taxonomic purpose, we applied the matrix-assisted laser desorption/ionization mass spectrometry with time-of-flight to identify 64 environmental AEFB (SDF for Solo do Distrito Federal) and compare the results with those obtained using 16S rRNA gene sequencing. Concordance between the two methods was observed for 93,75% samples at the genus level. Strains were clustered between 2 genera (family Bacillaceae): Bacillus, the most prevalent, and Lysinibacillus. Two other genera, Brevibacillus and Paenibacillus (family Paenibacillaceae) were also distinguished. Gene similarity discriminated an additional genus (Rummeliibacillus). At the species level, the genotyping method achieved superior capacity identifying 93,75% strains. Among 31 strains identified at the species level by protein profiling, 61.29% coincided and both, protein and gene profiling, placed other 32.25% strains within groups of closely related species of Bacillus bearing two or even more species alternatives within the same affiliation cluster. These results suggested the applicability of the score and sequence similarity ranges in a complementary way for initial identification and clustering of closely related samples inside these 64 SDF strains. Our assignments are useful because they clearly identify the genera and restrict the identity of a strain to one or two possible species in the genera, thus clarifying their genetic interrelationships. This study also stresses that combining phenotypic and genotypic methods into polyphasic approaches is essential for a robust assignment of the remarkable genetic and ecological diversity of AEFB.